An analysis of Cameroon's energetic system, 2001–2010. Issue 3 (4th March 2017) - Tamba, Jean Gaston
ABSTRACT: Cameroon is a poor country aiming to become an emerging country in horizon 2035. The energy sector is one of the key factors for economic growth. This article aims at analyzing the energy sector in Cameroon, taking into account energy potential, the energy structure and current energy policy in the sector. In spite of its high energy potential, the results show that accessibility, availability and affordability of energy are the main factors hindering energy development in different economic sectors of Cameroon. Thus, little progress has been made in improving energy supply due to a number of reasons, especially poverty.